2016
DOI: 10.1007/s12199-016-0531-5
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects on pulmonary function in young healthy adults exposed to traffic-related air pollution in semi-closed transport hub in Beijing

Abstract: Objectives Transport hub is an important part of urban comprehensive transportation system. Traffic-related air pollution can reach high level because of difficulty of diffusion and increase of emission in transport hub. However, whether exposure in this semi-closed traffic microenvironment causes acute changes in pulmonary function of commuters still needs to be explored. Methods Forty young healthy adults participated in this randomized, crossover study. Each participant underwent 2 h exposure in a designate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 26 publications
1
14
1
Order By: Relevance
“…Although there is strong evidence of a short-term association between outdoor air pollution and reduced pulmonary function for general population studies in adults, our model estimates did not support effects of ambient BC or PM2.5 on pre-bronchodilator function, or of indoor or ambient exposures on post-bronchodilator function (Chen et al. 2017; Huang et al. 2016; Lepeule et al.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Although there is strong evidence of a short-term association between outdoor air pollution and reduced pulmonary function for general population studies in adults, our model estimates did not support effects of ambient BC or PM2.5 on pre-bronchodilator function, or of indoor or ambient exposures on post-bronchodilator function (Chen et al. 2017; Huang et al. 2016; Lepeule et al.…”
Section: Discussioncontrasting
confidence: 69%
“…Exposures to PM2.5 have also been consistently associated with decreases in pulmonary function in general population epidemiologic studies (Chen et al. 2017; Huang et al. 2016; Lepeule et al.…”
Section: Introductionmentioning
confidence: 97%
“…Similar evidence has been found in other cities such as Seoul and New York . While the health effects of underground air pollution have received considerably less attention, several studies suggest that subway PM has the same or even greater adverse health effect than ambient PM …”
Section: Introductionsupporting
confidence: 68%
“…6 While the health effects of underground air pollution have received considerably less attention, several studies suggest that subway PM has the same or even greater adverse health effect than ambient PM. [7][8][9] A review of the "Environmental Burden of Disease in Europe" ranked noise as the second greatest environmental risk factor to health, contributing to 8% of the burden of disease ascribable to environmental factors. 10 Moreover, several studies indicated that subway noise levels exceed the recommended community exposure level (55 dB) 11,12 and might result in health impairments.…”
Section: Introductionmentioning
confidence: 99%
“…Among the sources of pollution in cities, pollutants emitted by the car have been identified as a major cause of air pollution. The major components of such emissions include carbon monoxide (CO), carbon dioxide, volatile organic compounds, nitrogen oxides, particulate matter, and the others [ 6 9 ]. CO is the primary component of emissions from light-duty vehicles, and comprises approximately 77% of all pollutants emitted in terms of concentration [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%